THE ASSESSMENT OF BANKRUPTCY RISK OF COMPANIES FROM THE SECTOR OF DRYING AND STORAGE OF CROPS AND PLANTS - Milić, Dragan; Tica, Nedeljko; Zekić, Vladislav; Popov, Milana; Šepa, Anja; Mihajlov, Zlata; Tekić, Dragana; Novaković, Tihomir (Journal on Processing and Energy in Agriculture, 2021)
Contemporary market conditions make all business entities confront various risks – credit risk, liquidity risk, cash flow risk and market risk. Companies should predict these particular business risks and manage them adequately in order to minimize their influence. The assessment of creditworthiness and bankruptcy risk has a major role in the process of prediction and management of company risks. The creditworthiness of companies presents their ability to meet financial obligations to their creditors contemporary business conditions recognize several methods for assessment of credit ability of entities. One of the most commonly used models for credit ability valuation, as well as prediction of bankruptcy likelihood in a company is the Altman's Z-score model. The main scope of this article is the assessment of bankruptcy risk by using Altman's Z-score model for the group of companies from the agricultural branch of drying and storage of fruit.
Keywords: risk, bankruptcy, credit ability, Z-score model